Derecho humano al agua potable - Angulo González, Carlos (2005)
The present titled investigation word "Human right to the drinkable water", was development with the objective of to foment and to recognize the access to the drinkable water, as universal, indivisible and non prescription human right; for it, we accessed to different investigations carried out by government organisms, civil society and people in the tapie. The supply of insufficient and inadequate drinkable water that imply risks represents a constant problem about the world population's health. The World Organization of Health (WOH) estimates that 80 % of all the illnesses in the world in development, are caused by the lack of clean water and appropriate reparation, being mainly this one ofthe main causes ofillnesses deaths in the children. The dirnensions of the impacts to the health that supposes do not have access to water under good health conditions in our populations are already undeniable. In spite of the contributions of the scientific and technological progress, the water continues being a problem; for this reason, in the context of the creation of a world every time more integrate, we are not able to more than to adopt a political optics to organize the efforts that converge in the satisfaction of this basic necessity for all and each one of the inhabitants of our country. The drinkable water is a vital resource for the human being and the right to the drinkable water and the reparations is integral part of the officially grateful human right in the different international events. It as never been considered the water like what is really: A very common one universal good, the humanity's vital patrimony. The access to the water should be considered as a basic, individual and collectively inalienable right. In front of this, it should be opted by a new culture of the development sustainable in matter of waters. If we think that the forest is not a simple wooden warehouse, then our rivers, aquifer, and lakes are simple warehouses of water. We should understand them like social, cultural, environmental values, also of the productive values that represent short term. Integrate this group ofvalues is to focus the treatment of our ecosystems from a new human rights to the water.